Profile of Critical Thinking Skills in Elementary School Students - Masithoh, Siti; Widodo, Wahono; Mustaji (Papanda Publisher, 2025)
This study aims to analyze the profile of critical thinking skills among upper-grade elementary school students by examining three core indicators: question formulation, strategy planning, and decision evaluation. A descriptive quantitative approach was employed, involving 100 fifth and sixth grade students in a Jakarta elementary school. Data were collected using a validated critical thinking test and Likert-scale questionnaires administered to students and teachers. Triangulation techniques were applied by combining test results, questionnaires, and structured classroom observations. The results showed that students performed very well in formulating questions (mean score = 80), moderately in planning strategies (mean score = 65), and poorly in evaluating decisions (mean score = 58). Questionnaire and observation data reinforced these findings, highlighting students' tendency to seek direct answers rather than explore multiple solutions. Teachers were observed to dominate classroom interactions, which limited students’ reflective thinking opportunities. This research emphasizes the need for instructional innovations, particularly through the implementation of problem-based learning and reflective discussions, to foster students’ ability to critically analyze and evaluate information. Furthermore, the findings provide practical implications for educators and policymakers to design learning environments that encourage autonomy, inquiry, and higher-order thinking skills among elementary students. The study provides comprehensive insights into how critical thinking develops in elementary students and suggests strategies for more effective curriculum implementation.